2015
DOI: 10.1016/j.ijgo.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenecks in the implementation of essential screening tests in antenatal care: Syphilis, HIV, and anemia testing in rural Tanzania and Uganda

Abstract: Our findings reinforce essential screening as a missed opportunity, caused by a lack of integration of funding and support for comprehensive antenatal care programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 15 publications
1
59
0
Order By: Relevance
“…The main reason for concomitant use of these drugs is the lack of knowledge among health care providers in the ANCs. Lack of integration of antenatal care services including IPTp and PMTCT in the health facilities is also a contributing factor for irrational use of SP and co-trimoxazole in HIV-infected pregnant women 26,27…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for concomitant use of these drugs is the lack of knowledge among health care providers in the ANCs. Lack of integration of antenatal care services including IPTp and PMTCT in the health facilities is also a contributing factor for irrational use of SP and co-trimoxazole in HIV-infected pregnant women 26,27…”
Section: Discussionmentioning
confidence: 99%
“…Duber et al found that vertical programs, even on the scale of PEPFAR, may not impact health outcomes that were not specifically targeted on a national level [12]. Attempts have been made to integrate donor-funded HIV prevention, care, and treatment programs into national health systems to ensure efficiency and sustainability, including: TB [13••, 14], maternal-child health (MCH) [15–20], cervical cancer screening [21], sexually transmitted infection (STI) [16, 22], and family planning [23, 24] programs. In addition, ART has increased the life expectancy of people living with HIV, and HIV is now considered a chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the WHO released guidelines that increased the recommended contacts to eight visits [10], although this has not yet been widely adopted as a measure of coverage. Studies on quality-adjusted coverage have used both one visit and four visits to quantify ANC coverage, which is based typically on maternal self-report in household surveys [11][12][13][14][15][16][17][18][19]. Facility measures have similarly followed WHO guidance on the expectations for ANC and have generally focused on inputs to care, with studies that define structural quality measures for health facilities such as functional diagnostics and medications [11,15,16].…”
Section: Viewpoints Research Theme 1: Countdown Coveragementioning
confidence: 99%